2021
DOI: 10.1002/ajh.26193
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis is associated with worse survival in children with acute lymphoblastic leukemia: A report from CYP‐C

Abstract: There are conflicting data about whether the development of cancer‐associated thrombo‐embolism (TE) negatively impacts survival in children. The objective was to determine whether TE during treatment was associated with overall survival (OS) and event‐free survival (EFS) in children with acute lymphoblastic leukemia (ALL). We performed a population‐based retrospective cohort study using the Cancer in Young People‐Canada registry. Children <15 years of age were diagnosed with de novo ALL (2000–2016). The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Conflicting data exists whether the development of cancer associated VTE has a negative impact on survival. In a population-based retrospective cohort study using the “Cancer in Young People Canada Registry”, 2006 children < 15 years of age (median age 4 years) with the diagnosis of ALL (88.5% B-cell precursor ALL) were studied for VTE and survival outcomes ( 78 ). Thromboembolism occurred in 113 patients (5.6%) at a median time of 107 days (IQR 35–184) from ALL diagnoses.…”
Section: Thrombosis: Acute and Long-term Sequelaementioning
confidence: 99%
See 1 more Smart Citation
“…Conflicting data exists whether the development of cancer associated VTE has a negative impact on survival. In a population-based retrospective cohort study using the “Cancer in Young People Canada Registry”, 2006 children < 15 years of age (median age 4 years) with the diagnosis of ALL (88.5% B-cell precursor ALL) were studied for VTE and survival outcomes ( 78 ). Thromboembolism occurred in 113 patients (5.6%) at a median time of 107 days (IQR 35–184) from ALL diagnoses.…”
Section: Thrombosis: Acute and Long-term Sequelaementioning
confidence: 99%
“…Patients with VTE had worse overall survival with a HRa for death of 2.61 (95% CI 1.62–4.22) p < 0.001) and EFS (HRa of death, relapse, second malignancy: 2.03 95% CI 1.35–3.05 p = 0.001) compared to patients without VTE. Thromboembolism was associated with significantly lower overall survival and event-free survival in children with high/very high-risk ALL (HRa 2.90, 95% CI 1.79–4.72, p < 0.001 and HRa 2.02, 95% CI 1.30–3.12 p = 0.002, respectively) ( 78 ). Omission of asparaginase can result in inferior leukemic survival.…”
Section: Thrombosis: Acute and Long-term Sequelaementioning
confidence: 99%
“…Thrombosis occurs in up to 36% of pediatric patients with ALL, many of which occur during induction remission ( 28 ) with a median time of 107 days ( 4 ). A recent study demonstrated an increased risk among high/very high-risk leukemia patients (8.6%) vs. standard/low-risk patients (3.5%) ( 4 ).…”
Section: Clinical Casementioning
confidence: 99%
“…Thrombosis occurs in up to 36% of pediatric patients with ALL, many of which occur during induction remission ( 28 ) with a median time of 107 days ( 4 ). A recent study demonstrated an increased risk among high/very high-risk leukemia patients (8.6%) vs. standard/low-risk patients (3.5%) ( 4 ). Patients with ALL are at particular risk for VTE due to multiple risk factors at diagnosis and throughout induction therapy such as endothelial damage from central venous catheter insertion, the inherent prothrombotic state associated with cancer, as well as pro-thrombotic medications that are administered together during induction therapy including asparaginase, corticosteroids, and anthracyclines ( 8 ).…”
Section: Clinical Casementioning
confidence: 99%
See 1 more Smart Citation